Characterization of the long‐distance dispersal of Johnsongrass (Sorghum halepense) in a vegetated irrigation channel. (17th September 2018) - Rudi, Gabrielle; Bailly, Jean‐Stéphane; Belaud, Gilles; Vinatier, Fabrice
Abstract: Hydrochorous dispersal may play a major role in the propagation of weeds such as Sorghum halepense (Johnsongrass). However, the long‐distance dispersal of this weed via agricultural intermittent channel networks, such as irrigation channels, has been poorly studied. In this study, we focused on a seed dispersal kernel obtained after an irrigation event in a vegetated channel. The main objectives of the study were to highlight the specificities of irrigation channels in relation to seed transport and investigate hydraulic factors and microscale channel features associated with the deposition of seeds along the channel. Our results showed that despite very different flow and morphological conditions compared with natural waterways, seeds of Johnsongrass were able to travel hundred meters at the scale of one irrigation event. This is likely due to the floating ability of more than 50% of the Johnsongrass seeds. A Regression Tree algorithm, which explained 72% of seed deposition variability, showed the importance of the channel features such as the width of the section and the hydraulic structures, sluice gates and culvert, to explain the patterns of seed deposition. A complex role of the emergent vegetation was highlighted. The results suggest that a threshold of vegetation density should be reached to enhance seed deposition. The results indicate that the spread of existing Johnsongrass populations could be limited by preserving existing hydraulic structures or maintaining areas where the density of terrestrial vegetation is sufficient to enhance seed retention downstream.